The Albanian Enforcement System - Flutura Kola (LeXonomica, 2021)
This article presents an overview of the Albanian legal system of enforcement in the civil and commercial area. Its purpose is not only to identify the enforcement system in Albania and the characteristics of each enforcement title but also to compare it with that of the Brussels IA Regulation. The article concludes that the Albanian enforcement system is built on the spirit of the European system and is very similar to several European countries. However, the range of foreign enforcement titles that can be recognized and enforced in Albania is narrower than that provided in the European Union countries. Therefore, it should be expanded to include, in addition to irreversible judgments, other European enforcement acts, such as European Payment Order, Settlement Agreements, Authentic instruments, etc.Povzetek. V tem članku je predstavljen pregled albanskega pravnega sistema izvršbe na civilnem in gospodarskem področju. Njegov namen ni le opredeliti sistem izvršbe v Albaniji in značilnosti posameznih izvršilnih naslovov, temveč ga tudi primerjati s sistemom iz Uredbe Bruselj Ia. Avtor ugotavlja, da je albanski sistem izvršbe zgrajen v duhu evropskega sistema in je zelo podoben več evropskim državam. Vendar je nabor tujih izvršilnih naslovov, ki se lahko priznajo in izvršijo v Albaniji, ožji kot v državah Evropske unije. Zato bi ga bilo treba razširiti tako, da bi poleg pravnomočnih sodnih odločb vključeval tudi druge evropske izvršilne naslove, kot so evropski plačilni nalog, sporazumi o poravnavi, verodostojne listine itd.